Faktor-Faktor Yang Mempengaruhi Firm Performance Pada Perusahaan Manufaktur Di BEI - Dhanendra, Sofia Prima Dewi (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
The purpose of this study is examine the analysis of factors affecting firm performance ofmanufacture companies listed on Indonesia Stock Exchange for the period 2015-2017.Sample was selected using purposive sampling method amounted to 65 companies. Data processing techniques usingmultiple regression analysis what helped by EViews program (Econometric Views) and Microsoft Excel 2016.The result of this study shows that partially liquidity and growth have positive effect on firm performance, while capital structure and inventory turnover have no effect on firm performance. This study shows that simultaneously liquidity, capital structure, growth and inventory turnover have an effect on firm performance